Study of prevalence of hypertension in an adult population of age group 40 to 60 years in an urban slum of Mumbai, Maharashtra, India - Rathod, Neeta Dilip; Lilare, Rushali Rajan (International Journal Of Community Medicine And Public Health, 2018)
Background: Hypertension is one of the commonest health related risk factor in India, with the largest contribution to burden of disease and mortality. Awareness of hypertension in India is low while appropriate treatment and control among those with hypertension is even lower. This mainly effects the middle age adult populations especially in urban slum area are more vulnerable for hypertension as they are so busy with their job responsibilities, family commitments, economic stress etc. If hypertension is detected early it is possible to minimize the risk of heart attack, heart failure, and stroke and kidney failure. An estimated 18 per cent of men and 13 per cent of women with high blood pressure are not receiving treatment that could protect them from an early death. So it is necessary to study the prevalence of hypertension in adult population of 40 to 60 years in an urban slum and to study the socio- demographic profile of this population. Methods: A cross-sectional study was carried out in the field practice area of the T. N. Medical College, Mumbai during the period of July 2015 to June 2016. A total 350 participants in the age group of 40 to 60 years using systematic sampling technique from urban slum area were interviewed and examined. A pre-tested interview tool was used to collect necessary information. Blood pressure <120/80 mmHg (normal), 120/80 to 139/89 mmHg (pre hypertension) and >140/90 mmHg (hypertension). Results: Out of the 350 participants, 148 (42.3%) participants had normal blood pressure and 81 (23.1%) participants had pre-hypertension, 79 (22.6%) participants had stage I hypertension and 42 (12.0%) participants had stage II hypertension. Conclusions: Prevalence of hypertension and pre-hypertension was 34.5% and 23.1% respectively. Various factors like gender, increasing age, low physical activity (exercise), high BMI, history of addiction, history of extra salt intake and family history of hypertension was associated with hypertension.